The effects of kratom (Mitragyna speciosa) on metabolic syndrome-related parameters: a systematic review and meta-analysis - Rayanakorn, Ajaree; Apisitwittaya, Pattarachon; Lee, Shaun Wen Huey; Yaja, Kantirat; Inpan, Ratchanon; Na Takuathung, Mingkwan; Koonrungsesomboon, Nut (Frontiers in Pharmacology, 2025)
BackgroundMitragyna speciosa Korth. [Rubiaceae] is a tropical plant with opioid-like properties used for its metabolic altering effects, but data on the metabolic effects are lacking. This systematic review and meta-analysis aim to examine the effects of kratom use on parameters related to metabolic syndrome (MetS) in humans.MethodsPubMed, Web of Science, Embase, and Cochrane Library databases were searched from inception to 6 September 2024 to identify eligible analytical studies examining the association between kratom consumption and metabolic effects. The effect estimates were summarized as mean differences (MDs) with 95% confidence intervals (CIs) and pooled using random-effects models.ResultsFive cross-sectional studies were included. The meta-analysis involving 1,458 adults observed significantly lower levels of serum low-density lipoprotein cholesterol (LDL-c) (MD -0.25-0.21 mmol/L; 95% CI: −0.39, −0.02), triglyceride (MD -0.17 mmol/L; 95% CI: −0.25, −0.09), while high-density lipoprotein cholesterol (HDL-c) levels increased (MD 0.07 mmol/L; 95% CI: 0.03, 0.11). Body mass index was also lower in adults using kratom when compared to the control group (MD -1.52 kg/m2; 95% CI: −2.81, −0.23).ConclusionKratom use in the adult population was associated with lower LDL-c, TG, BMI, and higher HDL-c levels. However, the total cholesterol and blood sugar lowering effects were not statistically significant. The findings suggest that kratom use may have a protective effect against certain metabolic risk factors. Further investigations particularly longitudinal studies with larger sample sizes are required to confirm these findings.Systematic Review Registrationidentifier CRD42024600702